Limbic Encephalitis Driven by a Pleural Mesothelioma: A Paraneoplastic Complication - Jacob O. Day; Adam J. Zeman (Middle East Journal of Cancer, 2016)
Paraneoplastic neurological syndromes have only been described with pleural mesothelioma in five cases. We have described a 72-year-old man who developed anterograde amnesia 27 months after diagnosis of epithelioid pleural mesothelioma. Investigations revealed a limbic encephalitis with no alternative causes identified. Limbic encephalitis is a classical paraneoplastic syndrome and presentation within five years of a cancer with no other causes identified is sufficient to diagnose a paraneoplastic etiology. This is the first case of isolated paraneoplastic limbic encephalitis driven by a pleural mesothelioma.